2020
DOI: 10.31234/osf.io/b2mvg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptual processing links autism and synesthesia: a twin study

Tessa Marije van Leeuwen,
Lowe Wilsson,
Hjalmar Nobel Norrman
et al.

Abstract: Background. Synesthesia occurs more commonly in individuals diagnosed with Autism Spectrum Condition (ASC) and is associated with autistic traits and autism-related perceptual processing characteristics, including a more detail-focused attentional style and altered sensory sensitivity. Furthermore, autistic traits and autism-like sensory sensitivity show a synesthesia-dosage effect, since they increase with the amount of synesthesia types in synesthetes and with the degree of synesthesia (how consistently colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(84 reference statements)
1
1
0
Order By: Relevance
“…A genetic link between synesthesia and autism or autistic traits is in line with the nding of high prevalence of both synesthesia and autism in a family study (9). Our results also correspond to the outcomes of a previous study conducted by our group in a different, smaller twin cohort, showing that twins with more consistent grapheme-color associations assessed with an objective synesthesia test scored higher on the attention to detail domain of the AQ, compared to their co-twins (32). This latter study indicated an association between the degree of (sub-threshold) synesthesia and the attention to detail domain of the AQ when implicitly controlling for all factors shared by twins, underlining the importance of factors that are not shared by twins in this association, but without being able to differentiate non-shared genetic from non-shared environmental factors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A genetic link between synesthesia and autism or autistic traits is in line with the nding of high prevalence of both synesthesia and autism in a family study (9). Our results also correspond to the outcomes of a previous study conducted by our group in a different, smaller twin cohort, showing that twins with more consistent grapheme-color associations assessed with an objective synesthesia test scored higher on the attention to detail domain of the AQ, compared to their co-twins (32). This latter study indicated an association between the degree of (sub-threshold) synesthesia and the attention to detail domain of the AQ when implicitly controlling for all factors shared by twins, underlining the importance of factors that are not shared by twins in this association, but without being able to differentiate non-shared genetic from non-shared environmental factors.…”
Section: Discussionsupporting
confidence: 91%
“…We used dimensional de nitions of both synesthesia and autism, rather than binary de nitions based on diagnostic criteria. This approach is justi ed a) because it allows modelling more variance (also between people not ful lling the criteria for synesthesia or autism), b) because autism is de ned as the extreme end of continuously distributed autistic traits (30) and c) because continuous de nitions of synesthesia have also been used successfully in previous research on the association between synesthesia and autism (21,22,31,32). For example, the number of different synesthesia types a synesthete has correlates positively with autistic traits, especially in the domain of attention to detail (21,22).…”
Section: Introductionmentioning
confidence: 99%